Optimal design and evaluation of survivable WDM transport networks. - Miyao, Y. (IEEE Journal on selected areas in communications)
This paper proposes an optimal design scheme for survivable wavelength-division multiplexing (WDM) transport networks in which fast restoration can be achieved by using predetermined restoration paths that are independent of failure locations and which have one to one correspondence with working paths. Integer programming-based design problems are formulated to optimally determine working and their corresponding restoration paths, the number of fibers in each span, and the number of optical cross connects (OXCs) in each node. In these optimization problems, total facility cost, which includes not only transmission cost but also cross connection, is minimized. This design scheme can handle the dedicated/shared allocation of spare resources and several parameters, such as the maximum available number of wavelengths per fiber Ω, the matrix size of each OXC, and cross-connection to transmission cost-coefficient ratio γ. Total fiber length, the total number of OXCs, etc., are evaluated from obtained design results for these options and parameters. Numerical examples show that the dependency of total fiber length and the total number of OXCs on γ is relatively small, and cross-connection to transmission cost ratios (γ times the total number of OXCs divided by total fiber length) in the dedicated and shared cases are almost the same for each combination of γ and Ω